Pengaruh Motivasi Kualitas, Motivasi Karir, Motivasi Ekonomi, Motivasi Sosial, Biaya Pendidikan pada Minat Mengikuti PPAk - Marta Permana, I Made Bagus Angga; Suartana, I Wayan (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
The purpose of this research is to know the influence of motivational qualities, economic motivation, career motivation, motivation and social costs of education on students ' interest to follow PPAk. The sample of this research is 61 respondents and use nonprobability sampling method and sampling purposive. Method of data collection using the questionnaire. Data analysis techniques, namely Multiple Linear regression analysis in testing the hypothesis. Conclusions in this study is the variable quality of motivation, career motivation, motivation of the economic and social motivations positive effect on students ' interest to follow PPAk. This means that the higher the motivation that is owned by the student then the higher interest follow PPAk. Unlike the variable tuition fees negatively influential on student interest follow PPAk which means the higher cost of education, the lower the interest follows a PPAk. Keywords : Quality motivation, career motivation, economic motivation, social motivation, educational cost, interest of students follow PPAk